Dictionary of Art Historians : a biographical and methodological database intended as a beginning point to learning the background of major art historians of western art history : a free, copyrighted, scholarly database for the use of researchers, students and the public (1996)
[Dt.:] Das Dictionary of Art Historians, www.arthistorians.info, kündigte eine neue Benutzeroberfläche, Datenstruktur und Benutzeroptionen an, die das Ergebnis eines einjährigen Redesigns sind. Das ursprüngliche Tool, eine Website seit 1996, wurde privat von Lee Sorensen, dem Bibliothekar für Kunst und visuelle Studien an der Duke University, entwickelt. Duke's Wired! Lab für digitale Kunstgeschichte und visuelle Kultur der Duke University förderte das Projekt ab 2016. Das neue DAH bietet durchsuchbare Daten zu mehr als 2400 Kunsthistorikern, Museumsdirektoren und Kunstschriftstellern der westlichen Kunst aus allen Epochen. Mehr als 200 akademische Websites haben auf das Projekt verlinkt; das Tool wurde als eines der wichtigsten Werkzeuge der Kunsthistoriografie bezeichnet. Das neue Dictionary of Art Historians wird im Laufe des kommenden Jahres weiter ausgebaut. Zu den neuen Funktionen, die veröffentlicht werden sollen, gehören: zusätzliche Filtermöglichkeiten auf der Seite "Explore"; die Möglichkeit, gefilterte Einträge in offene Datenformate zu exportieren; zusätzliche Ressourcen für die Verwaltung von Zitaten; neue Datenfelder; neue und aktualisierte Einträge. Das Dictionary of Art Historians nimmt weiterhin Beiträge entgegen. - [Engl.:] The Dictionary of Art Historians, www.arthistorians.info, announced a new interface, data structure, and user options, the product of a year-long redesign. The original tool, a website since 1996, was developed privately by Lee Sorensen, the art and visual studies librarian at Duke University. Duke’s Wired! Lab for digital art history & visual culture sponsored the project beginning in 2016. The new DAH offers searchable data on over 2400 art historians, museum directors, and art-writers of western art from all time periods. Over 200 academic websites have linked to the project; the tool has been called one of the core tools of art historiography. The new Dictionary of Art Historians site will continue to be developed over the coming year. New features to be released include: additional filtering capabilities on the “Explore” page; ability to export filtered entries in open data formats; additional resources for citation management; new data fields; new and updated entries. The Dictionary of Art Historians continues to accept contributions.